The Influence of Socially Responsible-HRM Practices on Retaining Talents - Ali Rawshdeh, Zainab; Zain, Zaher; Rosnita Ismail, Ida (International Journal of Engineering and Technology, 2018)
Corporate Social Responsibility (CSR) and Talent Management (TM) are at pivotal point in their development. However, the absence of rigorous studies that explore the relationship between Talent Retention and dimensions of CSR in the literature is surprising. Thus, the attempt of current research is to address this gap in the literature, by studying the effect of Socially Responsible Human Resource Management (HRM) practices on talent retention. And to contribute to the body of the literature by providing further insights about the importance of CSR to TM. Also, by adopting Socially Responsible HRM practices as different CSR practices that can affect organizational retention through different processes and impact stakeholders in different way. Furthermore, it answers recent calls for additional research about the impact of CSR on retaining talents, and on how integrating CSR into the culture of the organization could provide the organization with valuable conception in the talent retention.Â Â